Common mental disorders among women of reproductive age group in an urban area in Bengaluru - K. Sathyanarayana, Ramya; Manjunatha, Shashikala (International Journal Of Community Medicine And Public Health, 2019)
Background: Common mental disorders are commonly encountered in community settings, especially in women. The somatic symptoms often lead to repeated visits to health care practitioners without resolution of the problem. The knowledge of magnitude of common mental disorders and their associated factors has proved useful in psychiatric epidemiological research. Methods: A community based cross-sectional study was carried out among 480 randomly selected women in the reproductive age group using self-reporting questionnaire (SRQ-20), a validated tool developed by World Health Organisation. A standard cut-off score of 7 was used to identify women with common mental disorder. Data was analysed using descriptive statistics and suitable tests of significance in statistical package for social sciences (SPSS) v. 21.0. Results: The prevalence of common mental disorder was found to be 33.5% in the present study. Analysis showed that various socio-demographic characteristics of women like lower educational levels of women, widowed women, and women belonging to lower socio-economic class, belonging to joint family, lower body mass index had statistically significant association with common mental disorders. Conclusions: This study revealed that the prevalence of common mental disorders was high (33.5%) among the women of reproductive age group and there existed statistically significant association between common mental disorders and various socio demographic determinants.